Toxoplasma gondii chitinase-like protein TgCLP1 regulates the parasite cyst burden - Bando, Hironori; Murata, Yuho; Han, Yongmei; Sugi, Tatsuki; Fukuda, Yasuhiro; Bzik, David J.; Fox, Barbara A.; Kato, Kentaro (Frontiers in Cellular and Infection Microbiology, 2024)
Toxoplasma, an important intracellular parasite of humans and animals, causes life-threatening toxoplasmosis in immunocompromised individuals. Although Toxoplasma secretory proteins during acute infection (tachyzoite, which divides rapidly and causes inflammation) have been extensively characterized, those involved in chronic infection (bradyzoite, which divides slowly and is surrounded by a cyst wall) remain uncertain. Regulation of the cyst wall is essential to the parasite life cycle, and polysaccharides, such as chitin, in the cyst wall are necessary to sustain latent infection. Toxoplasma secretory proteins during the bradyzoite stage may have important roles in regulating the cyst wall via polysaccharides. Here, we focused on characterizing the hypothetical T. gondii chitinase, chitinase-like protein 1 (TgCLP1). We found that the chitinase-like domain containing TgCLP1 is partially present in the bradyzoite microneme and confirmed, albeit partially, its previous identification in the tachyzoite microneme. Furthermore, although parasites lacking TgCLP1 could convert from tachyzoites to bradyzoites and make an intact cyst wall, they failed to convert from bradyzoites to tachyzoites, indicating that TgCLP1 is necessary for bradyzoite reactivation. Taken together, our findings deepen our understanding of the molecular basis of recrudescence and could contribute to the development of novel strategies for the control of toxoplasmosis.